2004
DOI: 10.1002/cncr.20211
|View full text |Cite
|
Sign up to set email alerts
|

Beyond chronic myelogenous leukemia

Abstract: The myeloproliferative disorders (MPDs) are chronic malignant conditions originating from the clonal expansion of a multipotential hematopoietic stem cell.These diseases include polycythemia vera (PV), essential thrombocythenia, atypical chronic myeloid leukemia, idiopathic hypereosinophilic syndrome (HES), ag- Insight into the molecular pathogenesis of MPDs will improve the definitions of different disease categories and suggests that signal transduction inhibition is likely to be an increasingly important tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 84 publications
(131 reference statements)
0
10
1
Order By: Relevance
“…This selective activity has translated into remarkable response efficacy in patients with Ph chromosome positive CML (2,3). In addition to its inhibitory activity against cabl and bcr-abl, imatinib also inhibits two other tyrosine kinases, c-kit and platelet-derived growth factor receptor (PDGFR) (4,5,(15)(16)(17). In vitro inhibition of these kinases was achieved at concentrations similar to those required to inhibit bcr-abl, whereas minimal if any inhibition of other tyrosine kinases (e.g., epidermal growth factor receptor, JAK2, c-erbB2) was obtained at these concentrations (15).…”
Section: Discussionmentioning
confidence: 99%
“…This selective activity has translated into remarkable response efficacy in patients with Ph chromosome positive CML (2,3). In addition to its inhibitory activity against cabl and bcr-abl, imatinib also inhibits two other tyrosine kinases, c-kit and platelet-derived growth factor receptor (PDGFR) (4,5,(15)(16)(17). In vitro inhibition of these kinases was achieved at concentrations similar to those required to inhibit bcr-abl, whereas minimal if any inhibition of other tyrosine kinases (e.g., epidermal growth factor receptor, JAK2, c-erbB2) was obtained at these concentrations (15).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of an ABL kinase inhibitor, imatinib, has been established [21][22][23], and one contemporary issue is against which malignancies other than Ph+ leukemia imatinib is indicated [7,[24][25][26]. The TEL(ETV6) gene is fused with the ABL gene in atypical CML [27].…”
Section: Ablmentioning
confidence: 99%
“…Elevated plasma levels of PDGF found in patients with ET, PV, and PMF is thought to stimulate, along with several other cytokines, bone marrow fibrosis, a process that should be reversible with appropriate treatment (e.g., PDGFR inhibition) [3,36]. The clinical benefits of imatinib in PV have been reported in two studies where treatment with imatinib resulted in the reduction of phlebotomy requirements in some patients [37,38], thought to be the result of its non specific myelosuppressive effect.…”
Section: Philadelphia-negative Leukemias and Myeloid Disordersmentioning
confidence: 99%
“…In vitro studies have shown that in addition to Abl, imatinib potently inhibits platelet-derived growth factor receptor (PDGFR) and the class III tyrosine kinase KIT [2], leading to clinical studies of imatinib in other hematologic diseases where these molecular targets may be important [3]. …”
Section: Introductionmentioning
confidence: 99%